Grade V cherubism: A rare and aggressive entity - Karthikeya Patil; V G Mahima; S Sudhakar (Journal of Indian Academy of Oral Medicine and Radiology, 2009)
Cherubism is a non-neoplastic, rare, hereditary childhood disease of bone characterized by bilateral enlargement of the jaws caused by bone degradation and replacement by fibrous tissue. The affected child is reminiscent of the cherub portrayed in Renaissance art. We report the clinicopathological and radiographic features of cherubism and review of literature.